Pengaruh Subtitusi Proporsi Daun Pisang Kering (Klaras) dan Arang Sekam Terhadap Pertumbuhan dan Hasil Jamur Merang (Volvariella volvaceae) F3 Maja di Kabupaten Karawang - Iqbal Fajarudin; Darso Sugiono; Ani Lestari (Jurnal Ilmiah Wahana Pendidikan, 2021)
Merang mushroom (Volvariella Volvaceae) is one of the commodities of agricultural horticulture crop yield that has quite high economic value. Planting media become the most important thing for the farmer. Planting media that usually used by farmer is just the rice hay. The purpose of this research is to obtain plant media subtitution of dry banana leaf (klaras) and husk charcoal that most effective, so it would produce optimal growth and yield of Merang Mushroom. This experiment was implemented at Pasirmulya Village, Majalaya region, Karawang District at May untill july 2021. The research method that used is the experiment method with Randomized block design (RBK) single factor. There were 9 treatment l, which A (without treatment), B (Klaras 15%), C (Klaras 17%), D (Klaras 19%), E(Klaras 21%), F (Husk charcoal 15%), G (Husk charcoal 17%), H (Husk Charcoal 19%), I (Husk Charcoal 21%). Each of the treatment were repeated 3 times, so there were 27 Experiment units. If the data analyzed with analyze of variance and The test F rate at 5% showed significant results, then conducted to the continue test of Duncan Multiple Range Test (DMRT) at rate of 5% for acknowledging the best treatment. The experiment results showed that there were subtitution real effect of media dry banana leaf (Klaras) and husk charcoal towards the diameter of the crop body, and the total weight of yield by plots. Treatment I (Husk charcoal 21%) gave the highest results towards the diameter of crop body (2,40 mm), the total weight by plot (159,88 g).